THE EFFECT OF CHARACTERISTICS OF ACCOUNTING INFORMATION MANAGEMENT SYSTEM OF EMPIRICAL STUDY ON MANAGERIAL PERFORMANCE PT BANK RURAL LAND IN THE KABUPATEN TANAH DATAR - Ayu, Gusti - (Pendidikan Ekonomi, 2014)
This study was conducted to determine the effect of the characteristics of management accounting information systems on managerial performance in PT Bank Rural Tanah Datar. The population in this study is the manager at Rural Bank PT Tanah Datar with a sample of 36 respondents. The sampling technique used is the total sampling. Based on the results of hypothesis testing that is done then partially can be seen that the management accounting system which involves a series of broadscope, timeliness, aggregation and integration has a positive and significant influence on managerial performance of PT BPR in Tanah Datar, where significant levels <0.05 alpha . Then simultaneously broadscope, timeliness, aggregation and integration in the management accounting system has a positive and significant effect on managerial performance in PT Bank Rural Tanah Datar with significant value of 0.000 <0.05. From the research, it was found that broadscope, timeliness, aggregation and integration in the management accounting system had 81.2% influence on managerial performance in PT BPR in Tanah Datar, while 18.8% is determined by factors other than broadscope, timeliness, aggregation and integration in the management accounting system in this study. This result is known from the value of Adjusted R Square of 0.812 (81.2%). It is expected that the results of this study can serve as a reference for further research. And for researchers who want to examine the managerial performance of BPR manager suggested linking with other variables apart from broadscope, timeliness, agggregation and integration.